Perspectives and Knowledge about Fertility Preservation Strategies among Female Cancer Patients in Turkey. (8th February 2023) - Emirdar, Volkan; Karataşli, Volkan; Acet, Ferruh; Okay, Gulin; Gode, Funda; Karabulut, Alaattin; Arslan, Çağatay
Abstract : Objectives . To evaluate the knowledge level and perspectives of female cancer patients regarding fertility preservation techniques before gonadotoxic treatment. Material and Methods . This was a prospective observational survey-based study conducted between 2016 and 2020 in Izmir Economy University Medical Park Hospital. A total of 150 female cancer patients aged 18–42 years were included. The participants completed a 17-item questionnaire, developed by the research team to evaluate their knowledge and perspectives on fertility preservation techniques. Results . The mean age of the patients was 39.5 ± 4.9 years. Only 64.7% of the patients were referred to fertility counseling by a gynecologist, while 72.6% of the patients knew of the risk of infertility after cancer treatment. There was a significant correlation between the health status and cancer stage of the patient (p = 0.003 ). The estimated future chance of becoming pregnant spontaneously or through fertility preservation techniques was significantly higher in patients with a higher education level (p = 0.041 or 0.008, respectively). Satisfaction with the counseling process was reported as high or low by 66.7% or 20% of the patients, respectively. Conclusions . The rate of referral of reproductive-age cancer patients to fertility preservation counseling is still not satisfactory. Education level was the only variable significantly associated with a motivation to become pregnant after cancer treatment, either spontaneously or through fertility preservation techniques.